Cover Picture: Electrochemical Oxidative Csp3—H/S—H Cross‐Coupling with Hydrogen Evolution for Synthesis of Tetrasubstituted Olefins (Chin. J. Chem. 6/2019). Issue 6 (14th May 2019) - Lu, Fangling; Yang, Zengzhuan; Wang, Tao; Wang, Tianhao; Zhang, Yuying; Yuan, Yong; Lei, Aiwen
Abstract : The inside cover picture shows an electrochemical oxidative Csp 3 ‐H/S‐H activation with hydrogen evolution for the synthesis of tetrasubstituted olefins. This method features very high atom economy, besides hydrogen gas, under the base‐free, transition met‐al‐free, and oxidants‐free conditions, no other by‐products were generated. More details are discussed in the article by Lei et al . on page 547–551. Abstract : The inside cover picture shows an electrochemical oxidative Csp 3 ‐H/S‐H activation with hydrogen evolution for the synthesis of tetrasubstituted olefins. This method features very high atom economy, besides hydrogen gas, under the base‐free, transition met‐al‐free, and oxidants‐free conditions, no other by‐products were generated. More details are discussed in the article by Lei et al . on page 547–551.